Analisis Kinerja Jaringan Jalan Kota Dumai Menggunakan Pendekatan PKJI 2023 dan Pemodelan PTV Visum 25 - Ridho Imansyah, Muhammad (Jurnal Ragam Pengabdian, 2026)
Urban development and the increasing number of vehicles in Dumai City have led to a growing demand for an effective and sustainable transportation system. This condition may reduce road network performance due to the increasing traffic volume that is not balanced with adequate road capacity improvements. This study aims to evaluate road performance in Dumai City, analyze traffic movement distribution patterns, and determine appropriate improvement strategies for road segments experiencing performance degradation. The research method was conducted through road capacity and level of service analysis based on the Indonesian Highway Capacity Manual (PKJI) 2023 and transportation modeling using PTV Visum 25 on 14 selected road segments within the study area. The data used include traffic volume, road geometric characteristics, side friction conditions, and supporting transportation network data. The results show that most road segments still maintain good performance under existing conditions; however, performance degradation occurs under the 10-year projection scenario. Prof. M. Yamin Road is identified as the most critical segment, with a degree of saturation value of 0.89 and a Level of Service (LoS) E. The proposed widening scenario from 8 meters to 9 meters increases the road capacity from 2823 pcu/hour to 3096 pcu/hour, improving the road performance and supporting future traffic growth.